Effect of Incorporation of Vegetable Colour from Red Sandal (Pterocarpus santalinus) on Acceptability, Colour Development and Growth of Tilapia (Tilapia mossambica) - P.T., Mathew; K., Gopakumar (Fishery Technology, 2025)
Red colour extracted from red sandal wood (Pterocarpus santalinus) when incorporated n fish feed is found to increase the acceptability of the feed. It imparted a pink colour o the whole fish as well as to the fish flesh. The fishes fed with coloured feed showed ncreased feed intake and growth rate.